Covid-19 – Clinical Presentation and Lab Investigations - Hegde Usha; H S Sreeshyla; A P Shirona; Priyanka Nitin; B R Premalatha (Journal of Multidisciplinary Dental Research)
Corona virus is a single stranded RNA virus that causes severe respiratory tract infection. In 2020, a novel form of Corona virus, 2019-nCoV has been isolated and is the cause of a worldwide pandemic with the number of cases ever rising and being the cause of morbidities. There is no specific presentation of this infection, with common presenting symptoms being fever, cough, breathing difficulties, throat irritation, sneezing, pneumonia and diarrhoea. It spreads through aerosols causing rapid spread. Hence, diagnosis of covid19 is challenging and the need of the hour, so that the infected people can be isolated and the spread can be prevented. The diagnosis of this infection is done by antibody detection test, antigen detection test and molecular methods. General precautions such as - wearing mask, avoiding contact with others, maintaining social distance, regular washing of hands with soap or sanitizing own hands and avoiding touching one`s own face are the key to its prevention and spread. Keywords: Antibody, Antigen, Covid19, Infection, Lab investigation, PCR, Molecular diagnosis